CONCEPTUAL METONYMY AND GRAMMATICALIZATION: A COGNITIVE REVIEW (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This paper explores the role of conceptual metonymy as a fundamental cognitive mechanism underlying grammaticalization processes. While traditional approaches to language change have largely emphasized metaphor as the primary source of semantic extension, recent developments in cognitive linguistics suggest that metonymy plays an equally significant, and in many cases more precise, role. Drawing on key theoretical frameworks in cognitive linguistics and grammaticalization theory, this study synthesizes existing research to demonstrate how metonymic processes operate within single conceptual domains, enabling gradual and systematic shifts from lexical meaning to grammatical function. The analysis highlights recurrent metonymic patterns such as action-to-result, process-to-state, and event-to-aspect, which are widely attested across languages. By integrating insights from scholars such as Radden and Kövecses, Heine, Hopper and Traugott, and Brdar, the paper argues that grammatical structures are not arbitrary but cognitively motivated. The findings contribute to a deeper understanding of the relationship between cognition and grammar, emphasizing that metonymy should be regarded as a central mechanism in language change and the development of grammatical categories.